The Relationship Between the Neutrophil to Lymphocyte Ratio, The Platelet to Lymphocyte Ratio, and Cardiac Syndrome X - Cao GY; Li JC; Wang WJ; Wu HB (Dove Medical Press, 2022)
Guang-Yun Cao,1 Jian-Chao Li,1,2 Wen-Jing Wang,1 Hai-Bo Wu1 1Department of Cardiology, Hebei General Hospital, Shijiazhuang, Hebei Province, 050051, People’s Republic of China; 2HeBei North University, Zhangjiakou, Hebei Province, 050051, People’s Republic of ChinaCorrespondence: Hai-Bo Wu, Department of Cardiology, Hebei General Hospital, 348 Heping West Road, Shijiazhuang, Hebei Province, 050051, People’s Republic of China, Tel +86 15128138630, Email wuhb929@163.comObjective: This study aims to investigate the relationship between the neutrophil to lymphocyte ratio (NLR), the platelet to lymphocyte ratio (PLR), and cardiac syndrome X (CSX).Methods: A total of 102 patients with CSX who were hospitalized in the Cardiology Department of our hospital from December 2018 to December 2020 were enrolled in the CSX group, and 102 subjects who underwent physical examinations during the same period were included in the control group. An automatic blood cell analyzer was adopted to detect the neutrophil count (NC), lymphocyte count (LC), and number of platelets (PLT) in the whole blood of the subjects in both groups, and the NLR and PLR were calculated. Electrocardiography was conducted on the subjects in both groups to detect whether any abnormality existed in the ST segment. The receiver operating curve (ROC) was used to evaluate the diagnostic value of each indicator of CSX, and multivariate logistic regression analysis was adopted for the analysis of the influencing factors.Results: No significant differences existed in age, gender, smoking history, or family history of diabetes mellitus, hypertension, and tumors between the two groups (p > 0.05). When compared with the control group, the NC, PLT, NLR, PLR, and rate of abnormality of the ST segment on the electrocardiogram were significantly higher, and the LC was significantly lower in the CSX group (p < 0.05). Multivariate logistic regression analysis showed that the ST-segment abnormality (3.95 [2.10∼ 7.41]; NLR > 2.21, 3.46 [1.87∼ 6.39]; and PLR > 119.77, 3.66 [1.99∼ 6.73]) was a correlated risk factor for the occurrence of CSX (p < 0.05).Conclusion: Both the NLR and PLR in patients with CSX were significantly elevated, and both have a certain predictive value for the occurrence of CSX and are expected to be effective biomarkers for CSX.Keywords: cardiac syndrome X, neutrophil to lymphocyte ratio, platelet to lymphocyte ratio, correlation analysis, inflammation